Wasathah al-Khilaf al-Ijtima'iy bi-sya'n al-Taghayyurat fi-Ittijah al-Qiblah fi-Masjid Nur al-Huda fi-Simpang Empat Qaryah Aceh Tamiang - mursyidin1 mursyidin (Jurisprudensi : Jurnal Ilmu Syariah, Perundangan-Undangan dan Ekonomi Islam, 2021)
The social conflicts that occurred in the community regarding the change in the direction of the Qibla at the Nurul Huda Mosque in Simpang Empat Village became a long-term problem. These measurements make the Simpamg Empat community divided into two groups, namely, there are groups that are pro (agree with the change in Qibla wine) and those who are against, causing problems that require mediation to resolve this conflict. This article discusses the dispute between these groups by observed the mediation and legal action in Simpang Empat. This article argues that mediation is failed when community take legal action as conflict resolution.